PRINCIPLES OF PREPARATION AND STANDARDIZATION OF DETAILS IN THE REQUIRED SIZE - Akbaraliyev , Azamatjon Oybekjon ugli; Kamoliddinov , Sardorbek Hamidullo ugli; Saidmurodov , Iskandar Abdugaffor ugli (Educational Research in Universal Sciences, 2023)
Newly designed machines and parts should be reliable, precise, durable, long service life, easy to assemble, high productivity, easy to control, small in size, aesthetically pleasing, and economical. The performance of the machine parts being designed is determined by their strength, uniformity, resistance to heat, corrosion and vibration. Detail performance is determined by its operating conditions. Depending on the conditions under which the detailing works, it is necessary to determine what condition to set and ensure that this condition is fulfilled.